2019
DOI: 10.15381/rivep.v30i1.15670
|View full text |Cite
|
Sign up to set email alerts
|

Detección fenotípica de mecanismos de resistencia antimicrobiana de Escherichia coli aisladas de infecciones entéricas de porcinos provenientes de granjas de producción tecnificada

Abstract: El objetivo del estudio fue detectar fenotípicamente los mecanismos de resistencia antimicrobiana de 36 aislados de Escherichia coli a betalactámicos, quinolonas y aminoglucósidos mediante la técnica de Kirby-Bauer. Se utilizaron 36 aislados de E. coli procedentes de porcinos de granjas tecnificadas, obtenidos durante el periodo 2010- 2015. Se utilizaron 15 antimicrobianos de importancia en medicina humana y veterinaria. Se detectó resistencia principalmente al ácido nalidíxico (89%, 32/36), cloxacilina (83%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Several studies were focused on a variety of livestock, with data about chicken in 3 studies, and of pigs, cattle and alpacas in 2 studies each; thus, 9 studies were considered in the analysis [44,52,54,62,63,64,66,67,68]. Of these, only 3 were total or partially developed using samples from Lima (Table 1, Figure 1).…”
Section: Livestock Recovered Escherichia Colimentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies were focused on a variety of livestock, with data about chicken in 3 studies, and of pigs, cattle and alpacas in 2 studies each; thus, 9 studies were considered in the analysis [44,52,54,62,63,64,66,67,68]. Of these, only 3 were total or partially developed using samples from Lima (Table 1, Figure 1).…”
Section: Livestock Recovered Escherichia Colimentioning
confidence: 99%
“…Of note, the presence of heavy metals such as arsenic, chrome, cadmium, lead, mercury or zinc, and other toxics such as polycyclic aromatic hydrocarbon has been widely described in different Peruvian areas [113,114,115,116]. The presence of ESBLs was reported in 3 studies [62,65,66], which were not considered in the analysis of AMR because the samples were directly screened for ESBL-producing Enterobacteriaceae. These studies showed the presence of ESBLs in samples from chickens, cows and pigs, reporting the presence of bla CTX-M-14 , bla CTX-M-15 and bla CTX-M-26 [62,65,66].…”
Section: Livestock Recovered Escherichia Colimentioning
confidence: 99%
See 1 more Smart Citation
“…15 Phenotypic assays can be employed in routine laboratory practice to detect the existence of acquired resistance mechanisms in nosocomial infections that are commonly isolated from hospitals and other healthcare facilities. 16 Phenotypic techniques are mostly comprised of culture-based or staining-based diagnostic procedures. Currently, blood culture is the accepted method for the diagnosis of AMR.…”
mentioning
confidence: 99%